Penyuluhan PHBS Pada Anak Sekolah Dasar di SDN 1 Dukuhmencek Sebagai Upaya Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat di Lingkungan Sekolah - Cahya Tribagus Hidayat; Noviyanti Citra A; Fawzi Nurrahman; Nafilatulbalqis Nafilatulbalqis; Choiria Firdatul U; Zunanda Handrie L; Dwi Puji Lestari; Rosidawati Ningsih; Dwi Resti Alfioni; Arifah Retno H; Tri Mukti Wulandari; Intan Yuniar Damayanti; Trisya Bella F (Jurnal Pengabdian Teknologi Informasi dan Kesehatan (DIANKES), 2023)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health status for everyone. Healthy conditions do not necessarily occur, but efforts must always be made to transition from an unhealthy to a healthy life and create a healthy environment. Providing counseling related to Clean and Healthy Behavior (PHBS) in schools is expected to be an effort to increase students' knowledge of the importance of carrying out Clean and Healthy Behavior efforts in daily life and in the school environment, as well as provide knowledge on how to make it happen so that caring student behavior can be realized.